Reverse Genetic Strategies in Caenorhabditis elegans: Towards Controlled Manipulation of the Genome - Howard A. Baylis; Rafael P. Vázquez-Manrique (The Scientific World Journal)
Caenorhabditis elegans has a complete annotated genome sequence that is augmented by increasing quantities of data from high-throughput postgenomic analyses. This has led to an increasing need to identify the biological functions of specific genes using reverse genetics, i.e., moving from gene to phenotype. Fundamental to this aim is the ability to alter the structure of particular genes by means that are not accessible to classical genetic strategies. Thus, one dream of C. elegans researchers is to establish a toolkit for the controlled manipulation of any loci within the genome. Although C. elegans is amenable to a wide variety of genetic and molecular manipulations, controlled manipulation of endogenous genes by, for example, gene targeting has proved elusive until relatively recently. In this review, we describe and discuss the different methods available for the inactivation and modification of endogenous loci with a focus on strategies that permit some measure of control in this process. We describe methods that use random mutagenesis to isolate mutations in specific genes. We then focus on techniques that allow controlled manipulation of the genome: gene modification by transposon mobilisation, gene knock-out mediated by zinc-finger nucleases, and gene targeting by biolistic transformation.